Factors affecting the level of debt in the US. The case of credit card market. - Fedorov, Artem (2020)
This thesis investigates the key factors that impact the level of credit card debt in the US. We hypothesize that demographic (age, years of education, ethnicity, occupation, and marriage), economic (income and property possession status) and attitudinal (financial literacy and attitude towards credit) factors jointly affect the level of the credit card debt of US households. The model adopted in the thesis is inspired by the research of Chien and Devaney (2001) and it consists of two vital steps: stepwise regression to select the key determinants of credit card debt level and Tobit model to evaluate the coefficients and significance of the variables. The main dataset employed for the analysis is the triennial Survey of Consumer Finances for 2016. The main value-added of this thesis is the incorporation of financial literacy, which was not subject to analysis in the previous surveys. Results indicate that age, marital status, income, real estate ownership status, favorable and neutral attitude towards credit, and high self-reported financial knowledge are the statistically significant determinants of credit card debt level for US households.